PENGARUH ELEMEN-ELEMEN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SOSIS SO NICE (Studi Kasus Pelanggan di Kota Semarang) - Rikhi Dimas Al Habsyi; Rodhiyah Rodhiyah; sari listyorini (Jurnal Ilmu Administrasi Bisnis, 2016)
One of the efforts to be made by the manufacturer to be able to attract customersand compete with other manufacturers is to build brand equity that consists of severalelements of brand awareness, perceived quality, brand association and brand loyalty.ThisStudy aims to determine the effect of brand equity on purchase decisions sausage so nice insemarang, either individually or simultan.Data used is primary data from 97 respondentswhere the number of respondents is determined by a formula Lemeshow and David.Respondents were taken by accidental sampling method.Data were analyzed using simplelinear regression and Multiple Linear regression.Result show that brand awareness, perceived quality, brand associations and brand loyaltypositive and significant influence on purchasing decisions, either individually orsimultaneously. Variables that have the most influence on purchasing decisions is brandassociations Suggested to the company to increase brand awareness, perceived quality,brand association and brand loyalty to increase sales.